TRANSFORMASI PENDIDIKAN ISLAM DARI DINASTI UMAYYAH KE ABBASIYAH DAN RELEVANSINYA TERHADAP SISTEM PENDIDIKAN ISLAM INDONESIA - Ririt Komariah; Sahudi Sahudi; Cucu Siti Robi’ah; Ai Silvi Nurhasanah; Shalahudin Ismail (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study discusses the transformation of Islamic education from the Umayyad Dynasty to the Abbasid Dynasty, the strategic role of Baitul Hikmah during the Abbasid Dynasty in the development of Islamic education, and its relevance to the modern education system in Indonesia. Baitul Hikmah functioned not only as a library, but also as a translation center, educational institution, scientific research center, and astronomical observatory. Its existence became a symbol of the intellectual advancement of Muslims, particularly through the translation movement of scientific works from various civilizations. This study employs a qualitative approach, relying primarily on literature review as the main source, which includes various written materials such as books, articles, websites, and other relevant sources that support the smoothness of the writing process. The collected data is then analyzed descriptively. This study shows that libraries during the Abbasid period played an important role in shaping literacy culture and integration between religious and general sciences. By emulating the Baitul Hikmah model, contemporary Islamic education can be directed toward an integrative, multidisciplinary, and science-based system, enabling it to respond to the challenges of the times in a more adaptive and progressive manner. This research is expected to contribute theoretically and practically to the development of libraries as centers of learning and the improvement of the quality of Islamic education.